Legal of Permission Folk Mining in Indonesia - Derita Prapti Rahayu; Faisal Faisal (Wacana Hukum, 2020)
Juridically the people's mining is recognized in the law. This paper will discuss  the regulation of people's mining permits in Indonesia that permision on folk mining regulated on the act number 04 year 2009 about coal mineral. The criteria and nature of community mining are the mining business activities of the local people, carried out simply and in a small way, not using sophisticated equipment, the production is sufficient for the daily needs of the miners, the extent is very limited. IPR is given for a maximum period of 5 (five) years and can be extended. Regents / mayors give IPR especially to local residents, both individuals and community groups and / or cooperatives, (2) Regents / mayors can delegate the authority to administer IPR as referred to in paragraph (1) to the camat in accordance with the provisions of the legislation, (( 3) To obtain an IPR as referred to in paragraph (1), the applicant must submit a request letter to the regent / mayor.